Some aromatic compounds from dichloromethane extract of Salicornia ramosissima. - Isca, Vera M. S. (2012)
Salicornia ramosissima J. Woods, is an annual halophyte, confined to saline habitats, widely distributed in the salt marsh of Ria de Aveiro (Portugal) and also present in many salt marshes of the Iberian Peninsula. Our interest in the phytochemical study of this specie, which belongs to the genus Salicornia and family Chenopodiaceae, is based on previous knowledge that plants of this genus presented compounds such as flavonoids, chromones and alkaloids which are well-recognized for their biological activities. Salicornia ramosissima was subject to some studies of growth conditions and salinity, but its phytochemical composition remains unknown. The analysis of the dichloromethane extract from S. ramosissima aerial parts allowed the isolation of some aromatic compounds, from which we present here their unequivocal structure elucidation.